Childhood atopy and mental health: a prospective, longitudinal investigation. Issue 2 (20th October 2016) - Goodwin, R. D.; Robinson, M.; Sly, P. D.; Holt, P. G.
Abstract : Background: Prior studies have suggested a relationship between atopy and mental health, although methodological barriers have limited the generalizability of these findings. The objective of this study was to investigate the relationship between early-life atopy and vulnerability to mental health problems among youth in the community. Method: Data were drawn from the Raine Study ( N = 2868), a population-based birth cohort study in Western Australia. Logistic regression and generalized estimating equations were used to examine the relationship between atopy at ages 1–5 years [using parent report and objective biological confirmation (sera IgE)], and the range of internalizing and externalizing mental health problems at ages 5–17 years. Results: Atopy appears to be associated with increased vulnerability to affective and anxiety problems, compared to youth without atopy. These associations remained significant after adjusting for a range of potential confounders. No relationship was evident between atopy and attention deficit hyperactivity disorder or externalizing problems. Conclusions: Findings are the first linking atopy (measured by both parent report and objective verification) with increased vulnerability to affective and anxiety problems. Therefore, replication is required. If replicated, future research aimed at understanding the possible biological and/or social and environmental pathways underlying these links is needed. Such information could shed light on shared pathways that could lead to more effective treatments for both atopy and internalizing mental health problems.